2020
DOI: 10.1002/cpp.2418
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effects of detached mindfulness and cognitive restructuring in obsessive‐compulsive disorder using ecological momentary assessment

Abstract: Ecological momentary assessment (EMA) has been shown to be a valid and sensitive measure of treatment effects in obsessive‐compulsive disorder (OCD). As part of a clinical trial, this EMA study deals with a comparison of two treatment conditions, that is, cognitive restructuring (CR) and detached mindfulness (DM). EMA data from n = 39 OCD patients were available from a randomized clinical trial on the effectiveness of CR and DM. Smartphone‐based EMA sampling spread over 4 days each before and after treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The data were quite noisy; however, approximately 28.11% (851/3027) of the noise was removed during data cleansing [ 58 ]. A separate study assessed the results of these psychotherapy interventions and found no significant differences between the detached mindfulness and cognitive restructuring therapies in the frequency of their use, perceived difficulty, or the experience of relief after treatment [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data were quite noisy; however, approximately 28.11% (851/3027) of the noise was removed during data cleansing [ 58 ]. A separate study assessed the results of these psychotherapy interventions and found no significant differences between the detached mindfulness and cognitive restructuring therapies in the frequency of their use, perceived difficulty, or the experience of relief after treatment [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ecological momentary assessment is accepted as an important and reliable evaluation in demonstrating the efficacy of treatment of OCD. 35 In this context, in a study, the authors compared the effectiveness of detached mindfulness (DM) and cognitive restructuring in patients with OCD received in a randomized manner to the treatment groups. As a result of this study, the researchers reported that DM and cognitive restructuring methods showed similar results.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this study, the researchers reported that DM and cognitive restructuring methods showed similar results. 35 In a controlled study in a randomized manner on patients with OCD, a study team compared the efficacy of the MCT with ERP in 100 patients diagnosed with OCD in an outpatient setting and planned to examine the treatment effect of 2 modalities, measured by Y-BOCS at the beginning, after the treatment period, and at 6 and 30 months follow-up. 16 In this ongoing registered trial, investigators aimed to see that the MCT would have a potential effect compared to the ERP which is the gold standard psychotherapeutic approach in OCD treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For the early diagnosis of tristimania, the current clinical diagnosis of tristimania has many obvious shortcomings, including patient denial, poor sensitivity and subjective bias, which can lead to inaccurate diagnosis results, thus affecting the timely treatment of patients and resulting in illness delay. In general, compared with language and facial expressions, physiological signals can relatively and objectively reflect the dynamic changes of the central nervous system and have been applied in various studies [3].…”
Section: Introductionmentioning
confidence: 99%